PENGARUH FREE CASH FLOW, PROFITABILITAS DAN INVESMENT OPPORTUNITY SET TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2019)
Free Cash Flow, Profitability and Investment Opportunity Set together affect the Dividend Payout Ratio. Free cash flow is excess cash in the company that can be distributed to shareholders in the form of dividends (Brigham and Daves, 2003). This distribution can be made after the company makes capital expenditures, such as purchases of fixed assets in cash. According to Jensen (2011) states that free cash flow has a positive effect on the dividend payout ratio. The higher the free cash flow, the higher the dividend payout ratio or vice versa. The results showed that Free Cash Flow, Profitability and Investment Opportunity set were positive and significant for the dependent variable